Community Training of Breadfruit Processing into Breadfruit Flour and Cookies as an Alternative of Wheat - Neny Rasnyanti.M Aras* (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Breadfruit (Artocarpus altilis) has the opportunity to become an alternative food in order to support food security by making flour from processed breadfruit. Yellow breadfruit tastes like flour. Cookies are usually made of wheat. Wheat has a higher content of calories, protein, fat and phosphorus than breadfruit flour while breadfruit flour has a higher content of vitamins, calcium, carbohydrates than wheat. This service program aims to provide training to empowerment and family welfare women on how to process breadfruit into breadfruit flour and make cookies of it. The service was held in December 2020 in Nipa-Nipa Village, Bantaeng Regency. This service program uses the Participatory Action Research (PAR) method. The results of breadfruit cake using the preference test showed satisfactory performance. This training will provide insight to PKK mothers so they can take advantage of the abundance of tribes in Bantaeng district. The existence of this training is expected to grow new small and medium enterprises in the context of developing regional souvenirs.